Exploring the Socio-personal Factors Associated with the Prevalence of Symptoms of Reproductive Tract Infections among Sexually Active Married Women in Ernakulam District of Kerala, India - Ann Merrin George; Leena Kunnath Chacko (Indian Journal of Community Medicine)
Background: Reproductive Tract Infections (RTIs)/Sexually Transmitted Infections (STIs) are the main cause of maternal mortality and morbidity in India. The prevalence of the symptoms of RTIs was found to be very high in community-based studies. However only a few studies have explored the factors associated with it. This study aims to determine the socio-personal factors associated with the prevalence of symptoms of RTIs among sexually active married women in Ernakulam district of Kerala. Material and Methods: The study adopted a cross-sectional approach and was conducted among 640 married women in the reproductive age group. Results: The prevalence of the symptoms of RTIs was found to be 56.9% and about 60.16% of them had experienced multiple symptoms. Multivariate analysis showed that those women living in the urban areas (OR: 0.49, 95% CI: 0.334, 0.719), having no previous history of obstetric/gynecological risk factors (OR: 1.89, 95% CI: 1.119, 3.19) and using both clothes and sanitary pads interchangeably during menstruation (OR: 0.46, 95% CI: 0.282, 0.734) were found to be at less risk of contracting RTIs. Conclusion: The use of sanitary pads along with cloth pads can be enhanced rather than only using reusable cloths during menstruation. Also, efforts to improve the reproductive health of the women and reduce the obstetric/gynaecological risk factors should be devised to curtail the peak of RTIs.